Social Identity and Legal Personality – Collective Entities as Legal Entities? - Miodrag Jovanović (University of Belgrade, 2016)
The paper argues that the legal-theoretical treatment of the issue of promoting certain collective entities to the status of legal entities cannot be satisfactorily accomplished within the methodological models of either Hart’s analytical jurisprudence or Kelsen's Pure Theory of Law. The question of the conceptualization of collective rights proves to be largely a question of justification rather than one of mere analysis or description. In this sense, the paper proposes to elucidate various aspects of the problem of the legal shaping of the social identity of relevant collective entities with the purpose of constructing legal personality. The first section of this paper briefly shows that the question of legal personality is a general problem of legal theory, and that there is consequently nothing specifically new about collective entities as potential legal entities. The second section of the paper considers in greater detail the social and legal "construction of diversity", on which the concept of collective rights is based. Finally, the paper suggests that the legal theory of collective rights can hardly accomplish these tasks without recourse to the methodological apparatus of both sociological and anthropological disciplines.